Clinical score to predict the risk of bile leakage after liver resection. Issue 1 (December 2016) - Kajiwara, Takahiro; Midorikawa, Yutaka; Yamazaki, Shintaro; Higaki, Tokio; Nakayama, Hisashi; Moriguchi, Masamichi; Tsuji, Shingo; Takayama, Tadatoshi
Abstract Background In liver resection, bile leakage remains the most common cause of operative morbidity. In order to predict the risk of this complication on the basis of various factors, we developed a clinical score system to predict the potential risk of bile leakage after liver resection. Methods We analyzed the postoperative course in 518 patients who underwent liver resection for malignancy to identify independent predictors of bile leakage, which was defined as "a drain fluid bilirubin concentration at least three times the serum bilirubin concentration on or after postoperative day 3, " as proposed by the International Study Group of Liver Surgery. To confirm the robustness of the risk score system for bile leakage, we analyzed the independent series of 289 patients undergoing liver resection for malignancy. Results Among 81 (15.6 %) patients with bile leakage, 76 had grade A bile leakage, and five had grade C leakage and underwent reoperation. The median postoperative hospital stay was significantly longer in patients with bile leakage (median, 14 days; range, 8 to 34) than in those without bile leakage (11 days; 5 to 62;P = 0.001). There was no hepatic insufficiency or in-hospital death. The risk score model was based on the four independent predictors of postoperative bile leakage: non-anatomical resection (odds ratio, 3.16; 95 % confidence interval [CI], 1.72 to 6.07;P < 0.001), indocyanine green clearance rate (2.43; 1.32 to 7.76;P = 0.004), albumin level (2.29; 1.23 to 4.22;P = 0.01), and weight of resected specimen (1.97; 1.11 to 3.51;P = 0.02). When this risk score system was used to assign patients to low-, middle-, and high-risk groups, the frequency of bile leakage in the high-risk group was 2.64 (95 % CI, 1.12 to 6.41;P = 0.04) than that in the low-risk group. Among the independent series for validation, 4 (5.7 %), 16 (10.0 %), and 10 (16.6 %) patients in low-, middle, and high-risk groups were given a diagnosis of bile leakage after operation, respectively (P = 0.144). Conclusions Our risk score model can be used to predict the risk of bile leakage after liver resection.